Evolution of Graphics-Development & Innovations - Somni, Rohan; Jain, Tarush (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Graphics are now an integral part in many scientific, and entertainment fields. Radical discoveries and developments are still being made. Combinations of techniques and technology from different scientific fields are the primary reasons for these advancements. In this paper we highlight some of the key developments, and technological innovations that have taken place to enable graphical technology to progress to where it is today, covering both software for consoles as well as handheld devices and tablets. We attempt to be succinct, but technically so, in describing a few key aspects of applications and technologies which are now ubiquitous, or which will be in the near future. We describe both staples like DirectX and hardware tessellation as well as relatively new concepts like the Grid and Retina displays for smartphones.